1997
DOI: 10.1006/dbio.1997.8575
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Control of Murine GATA-3 Transcription by Promoter-Proximal Regulatory Elements

Abstract: GATA-3 is expressed in a temporally dynamic manner and fulfills vital functions during vertebrate fetal development. Homozygous mGATA-3 mutant embryos die at midgestation, thus complicating the analysis of its contribution to the development of specific cell fates in the many tissues where it is expressed during embryogenesis. We show here that the elements controlling GATA-3 regulation can be precisely refined, using transgenic mice, to discrete cis-acting domains: within 6 kb surrounding the transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 42 publications
6
42
0
Order By: Relevance
“…A previous study attempted to identify GATA-3 transcripts by primer extension analysis of the murine BW5147 thymoma and MEL erythroleukemia but did not included nontransformed T cell or tissue (1). Interestingly, exon 1a is located near a previously identified DNase-hypersensitive site that is present in BW5147 but not in C1300 (26).…”
Section: Figurementioning
confidence: 93%
“…A previous study attempted to identify GATA-3 transcripts by primer extension analysis of the murine BW5147 thymoma and MEL erythroleukemia but did not included nontransformed T cell or tissue (1). Interestingly, exon 1a is located near a previously identified DNase-hypersensitive site that is present in BW5147 but not in C1300 (26).…”
Section: Figurementioning
confidence: 93%
“…3 presents a side-by-side analysis of two GATA family members and two Pax family members in adult lymphoid (Ig and/or TCR ϩ ) and nonlymphoid tissues of the mouse and skate, respectively. GATA-3 in the mouse is expressed in several nonhemopoietic tissues in addition to T cells, under control of distinct sets of cis-regulatory sequences (40,41). Thus, GATA-3 expression in the skate would not be expected to be confined solely to TCR ϩ cells.…”
Section: Conservation Of Lymphoid Expression Patterns In Skate Ortholmentioning
confidence: 99%
“…Previously, it was reported that an ϳ2.5-kb genomic fragment, encompassing the murine GATA-3 promoter, its upstream region, the first exon, the first intron, and the untranslated part of the second exon, was sufficient to confer T cell specificity in vitro (8,9). In addition, the 3Ј end of the first intron of the human GATA-3 gene was found to be critical for the activity of a human GATA-3 promoter (10).…”
Section: Identification Of a T Cell-specific Regulatory Region In Thementioning
confidence: 99%
“…An ϳ2.5-kb genomic fragment encompassing several of the DNase I hypersensitivity sites is sufficient to support the expression of a reporter gene in a T cellspecific manner in vitro (8,9). A recent report showed that the T cell specificity of the human GATA-3 gene might be regulated by an upstream silencer and a positive cis-acting element, which is located in the 3Ј end of the first intron, however, neither of the regulatory elements was cell type-specific (10,11).…”
mentioning
confidence: 99%